Política Nacional de Alfabetização: possíveis implicações na formação do professor alfabetizador - Almeida, Fabiani Inês de (2022)
The present work is associated with the research line “Training processes, educational practices, differences”, of the Graduate Program in Education at the Federal University of Mato Grosso do Sul. From the formulated problem, it was defined as objective to investigate the possible implications present in the National Literacy Policy (PNA), seeking to analyze the intrinsic ideology in the policy discourse, as well as its possible implications in the formation of the literacy teacher and how this normative infers in society with perspectives that guide and define literacy. To this end, the documentary analysis was based on Decree n. 9.765/2019, which established the PNA and its explanatory manual, which expands the issues presented by the Decree. In view of this intention, the theoretical contribution used is based on the aegis of the theoretical current of Historical-Cultural Psychology and Historical-Critical Pedagogy whose investigation method is based on historical-dialectical materialism, thus considering, to unveil the appearances contained in the essence of the phenomenon , with the focus of transgressing the pseudo-concreticity presented by the immediate reality and analyzing the inherent contradictions of class society. The results found indicate that the advance of the extreme right in the country established educational policies aligned with market interests, whose bias is based on the perpetuation and hegemonization of capitalism. Furthermore, we found that the PNA embarks on a neoliberal conception, based on the Pedagogy of Competencies, whose technical-instrumental model limits critical thinking and the solid formation of a praxis that develops the maximum capabilities of human beings. In this context, the preliminary analyzes show that the PNA materializes the dehumanizing and recrudescent forms of education, fragments the conception of language, reducing the literacy process to the phonic method, as the only effective methodology for learning to read and write. With a pseudo-neutrality character, the scientific evidence presented by the document affirms the arbitrary position by dismissing other theoretical possibilities, pointing to the total silencing/deleting of all the contributions of researchers in the area of literacy throughout history. In this way, it is concluded that the PNA has implications for the initial and continuing education of teachers, having seen the emptying of the teaching profession and the secondaryization of artistic, philosophical and scientific knowledge, corroborating a fragmented and mechanical training, which restricts critical thinking and the development of the maximum capacities already developed by human beings. Keywords: National Literacy Policy; teacher training; literacy.